A modified basket catheter technique with semi-rigid ureterorenoscopy in the prevention of migration of proximal ureteral stones - Erdoğan, Abdullah; Keskin, Ercüment (The European Research Journal, 2021)
Objectives: Although proximal ureteral stones are common, some difficulties are encountered in semi-rigid ureterorenoscopy (URS) treatment, especially as a result of stone migration to the kidney. In this paper, we present a different use of a basket catheter for the treatment of proximal ureteral stones. Methods: Between September 2016 and January 2019, 101 patients over 18 years of age detected to have a maximum 15-mm proximal ureteral stone were retrospectively evaluated, and 93 patients fulfilling the criteria were included in the study. Semi-rigid URS and a modified basket catheter were used together in 44 patients while no auxiliary equipment was utilized for the remaining 49 patients. In the study group, a 3F zero-tip basket catheter was disintegrated and positioned in a way to capture and retrieve the stone from the semi-rigid ureterorenoscope. Results: No difference was found between the two groups in terms of age, body mass index, gender, and stone characteristics. The duration of operation was shorter in the basket catheter group (p < 0.001). The rates of stone migration, requirement to switch to flexible ureterorenoscopy (FURS), and double J-stent (JJ-stent) placement were significantly higher in the control group (p < 0.005). There were no significant differences between the two groups concerning operation success and complications (p = 0.068 and p = 0.772, respectively). Conclusions: The modified basket catheter technique with semi-rigid URS was successful in preventing the migration of proximal ureteral stones. This method can be considered as an alternative in cases where FURS is not available.